Asupan garam tinggi, lemak jenuh, dan kurangnya konsumsi buah-sayur sebagai determinan risiko Hipertensi di Kabupaten Pulau Morotai - Asri, Yuni; Ekawati, Ekawati (Universitas Muhammadiyah Magelang, 2025)
Background: Hypertension is a leading global health concern and a major cause of cardiovascular disease. Its prevalence continues to rise in Indonesia, particularly in rural regions. This study analyzed demographic, dietary, and lifestyle factors associated with hypertension risk in Pulau Morotai Regency. Methods: A cross-sectional study was conducted at Ir. Soekarno Regional Hospital from July to August 2025 among 90 hypertensive patients. Data on demographics, lifestyle, and diet were collected using structured questionnaires and medical records. The dependent variable was hypertension risk (“at risk” vs. “not at risk”), while independent variables included gender, age, smoking history, dietary pattern, salt intake, saturated fat intake, fruit and vegetable intake, and processed food consumption. Data were analyzed using IBM SPSS Statistics version 25 with chi-square tests. Sampling weights accounted for stratification, clustering, and unequal probability of selection to ensure representative estimates. Results: Most participants were older adults (90%) with unhealthy diets (84.4%), high salt intake (84.4%), frequent processed food (58.9%) and saturated fat consumption (58.9%), and low fruit and vegetable intake (53.3%). Hypertension risk was significantly associated with age, diet, salt, saturated fat, fruit and vegetable intake, and processed food (p < 0.001). Gender and smoking were not significant. Conclusion: Hypertension risk in Pulau Morotai is driven by age and modifiable dietary behaviors. Interventions should prioritize salt reduction, healthy eating, and dietary counseling.